Associations between sleep duration, midday napping, depression, and falls among postmenopausal women in China: a population-based nationwide study. Issue 5 (May 2021) - Zhou, Zonglei; Yu, Yu; Zhou, Ruzhen; Luan, Rongsheng; Li, Kunpeng
Abstract: Objective: To explore the independent and joint associations of sleep duration, midday napping, and depression with fall accidents in Chinese postmenopausal women. Methods: A total of 2, 378 postmenopausal women aged ≥ 45 years from the baseline survey of the China Health and Retirement Longitudinal Study were enrolled in the study. Each participant provided data on falls, sleep duration, midday napping by a self-reporting approach. We employed the Chinese version of the Center for Epidemiologic Studies Depression Scale to assess depression. Adjusted odds ratios (OR) and 95% confidence intervals (CI) were calculated to estimate the associations of predictor variables with falls using multivariate logistic regression. Results: Of the 2, 378 postmenopausal women, 478 (20.10%) reported falls in the preceding 2 years. Compared with sleep duration of 7 to 8 h/night, sleep duration of 5 to 6 h/night (OR, 1.49; 95% CI, 1.03-2.15) and of ⩽ 5 h/night (OR, 1.63; 95% CI, 1.18-2.25) were associated with a higher fall prevalence. However, no significant correlation was found between sleep duration of > 8 h/night and falls. Furthermore, participants with depression were more likely to report falls (OR, 1.78; 95% CI, 1.41-2.25) than their depression-free counterparts. The duration of midday napping was not independently associated with falls, but significant joint associations of sleeping ⩽ 6 h/night and no napping (OR, 1.72; 95% CI, 1.07-2.76) or napping > 60 minutes (OR, 2.14; 95% CI, 1.18-3.89) with more falls were found. Similarly, a combined status of sleeping ⩽ 6 h/night and depression was related to more falls (OR, 2.97; 95% CI, 1.86-4.74). Conclusion: The present study demonstrates that short sleep duration and depression are independently associated with more falls among postmenopausal women in China. Moreover, short sleep duration combined with no or long napping, short sleep duration combined with depression are jointly correlated with more falls. Future longitudinal studies are warranted to confirm these findings.